Formative Assessment in Macedonian Language Teaching Process for Primary Education in the Republic of Macedonia - Violeta Januševa; Jana Jurukovska (International Journal of Assessment Tools in Education)
In the Republic of Macedonia, the formative assessment, which represents a new paradigm in the assessment that focuses on the students as active participants in the teaching process, was established in 2007 as part of the Primary Education Project (PEP) by USAID (United States Agency for International Development). This research is focused on the analysis of Macedonian language teaching curriculum from first to ninth grade for primary education in the Republic of Macedonia, on the analysis of the suitability of the tasks for formative assessment in one Macedonian language textbook, as well as on the examination of students’ and teachers’ viewpoints, concerning various aspects of formative assessment in Bitola region of the Republic of Macedonia. From the analysis it could be seen that there is strong support of formative assessment by the authorized structures, and that there are many positive and negative aspects of the use of formative assessment in the Macedonian language teaching process. The reasearch has qualitative and quantitative paradigm and the methods for collecting and processing the data, and also for gaining scientific conclusion are analysis and synthesis. The instrument consists of two questionaires, one for students and one for teachers.